2012
DOI: 10.1002/ibd.22901
|View full text |Cite
|
Sign up to set email alerts
|

Performance of interferon-gamma release assays in patients with inflammatory bowel disease: A systematic review and meta-analysis

Abstract: While it remains difficult to determine superiority between the IGRAs and the TST, both are negatively affected by IST. Therefore, screening prior to initiation of IST should be considered. Nevertheless, it is imperative that all patients receive screening prior to anti-TNF therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 44 publications
2
42
0
Order By: Relevance
“…These results, being in agreement with other studies, suggests that IMM may not have an influence on these two tests [9,14,15,17]. On the contrary, some other studies as well as a recent meta-analysis showed a negative impact of immunosuppressive therapy both on the IGRA [6,[10][11][12][13] and the TST [9], probably due to a decrease of the absolute lymphocyte count [7] and/or of their CD8 portion [21]. The overall concordance between QFT-G-IT and TST was comparable to previous studies, although a higher concordance rate was observed in IMM group [6,[10][11][12][13][14][15]17].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…These results, being in agreement with other studies, suggests that IMM may not have an influence on these two tests [9,14,15,17]. On the contrary, some other studies as well as a recent meta-analysis showed a negative impact of immunosuppressive therapy both on the IGRA [6,[10][11][12][13] and the TST [9], probably due to a decrease of the absolute lymphocyte count [7] and/or of their CD8 portion [21]. The overall concordance between QFT-G-IT and TST was comparable to previous studies, although a higher concordance rate was observed in IMM group [6,[10][11][12][13][14][15]17].…”
Section: Discussionsupporting
confidence: 88%
“…However, the optimal strategy in IBD patients has not been yet well-defined as both TST and QFT-G-IT may be negatively affected by disease activity and/or treatment with immunomodulators (IMM), such as azathioprine and methotrexate [6][7][8][9][10][11][12][13][14][15][16][17]. The sensitivity and specificity of TST in the diagnosis of LTB can be limited by high disease activity, malnutrition, treatment with IMM, prior Bacille Calmette-Guerin (BCG) vaccination and/or exposure to environmental mycobacteria [8,9,18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, a systematic review showed that both positive IGRA and positive TST results were significantly influenced by immunosuppressive therapy. 22 The Hong Kong guideline for the TST cut-off value for LTBI diagnosis before anti-tumour necrosis factor treatment is an induration of >10 mm. 3 In the current study, we showed that the TST cut-off value that achieved better agreement between IGRA and TST results was 5 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Patients treated with IST had higher degree of disagreement (14.3%, k = 0.39), while the patients not treated with IST had a 100% conformity of the two tests. A systematic review and meta-analysis has evaluated the findings of IGRA tests [19] in IBD patients.…”
Section: Mycobacterium Tuberculosismentioning
confidence: 99%